In situ Generated Ruthenium Catalyst Systems Bearing Diverse N-Heterocyclic Carbene Precursors for Atom-Economic Amide Synthesis from Alcohols and Amines; Chemistry - An Asian Journal; Vol. 13, iss. 4 - Cheng Hua; Mao-Qian Xiong; Chuan-Xiang Cheng; Hua-Jing Wang; Qiang Lu; Hong-Fu Liu; Fu-Bin Yao; Cheng Chen; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen